Palm Fibers Effect on the Performance of a Conventional Solar Still - Kermerchou, Imad; Mahdjoubi, Idris; Kined, Chamseddine; Khechekhouche, Abderrahmane; Bellila, Abdelkader; Isiordia, German Eduardo Devora (ASEAN Journal for Science and Engineering in Materials, 2022)
The lack of drinking water is one of the most important. Solar distillation remains the simple and effective solution to solve this problem, but the yield of solar distillation is low. However, the thermal performance of the solar still is low. Several researchers have made various experimental modifications to improve thermal performance. In this experimental modification, palm fibers were introduced to improve the performance of a solar still. The results showed that when using palm fibers there was an improvement of 35.6 % compared to the conventional still.